Unleashing the Potential of Digital Marketing to Enhance Communication Effectiveness in Public Organizations in Indonesia - Ahmad Wahidiyat Haedar (PINISI Discretion Review, 2023)
Digital marketing has emerged as a powerful tool for organizations to effectively communicate their messages and engage with their target audience. While its significance has been widely recognized in the private sector, the potential of digital marketing remains underutilized in the context of public organizations in Indonesia. This study aims to explore the untapped opportunities and benefits that digital marketing offers to enhance communication effectiveness in public organizations within the Indonesian context. This research employs a qualitative approach, utilizing a combination of literature review, case studies, and expert interviews. The findings highlight that embracing digital marketing strategies can significantly contribute to improving communication outcomes in public organizations. By leveraging various digital channels such as social media, email marketing, search engine optimization, and content marketing, public organizations can establish stronger connections with citizens, disseminate information more efficiently, and increase public engagement. Furthermore, the study identifies several challenges that hinder the adoption of digital marketing in public organizations, including limited resources, organizational culture, and regulatory constraints. Overcoming these challenges requires a comprehensive strategy encompassing leadership commitment, capacity building, collaboration with digital marketing experts, and the development of clear guidelines and policies. This research emphasizes the need for public organizations in Indonesia to recognize and harness the potential of digital marketing to enhance communication effectiveness. By embracing digital marketing strategies, public organizations can establish themselves as transparent, accessible, and responsive entities, fostering citizen trust, participation, and ultimately contributing to better public services and governance..